Penerapan Aplikasi Google Family Link terhadap Penggunaan Gawai Berlebih pada Anak Usia Sekolah dengan Masalah Gangguan Proses Keluarga - Shofiana Haniffah; F X Bobby Tyas Prastyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Families with school-age children face various parenting challenges in the digital era, particularly due to the increasing use of gadgets among children. Excessive and uncontrolled gadget use may negatively affect communication, interaction, and family harmony, especially when parental supervision is limited. One strategy to support parents in managing their children’s digital activities is the utilization of the Google Family Link application. This study aimed to analyze the effectiveness of Google Family Link in reducing excessive gadget use among school-age children experiencing family process dysfunction. A family nursing case study approach was employed involving three families with school-age children who demonstrated difficulties in controlling gadget use. Data were collected through interviews, observations, questionnaires, and family nursing assessments. The findings revealed that all participating families experienced challenges in supervising their children’s gadget use, resulting in family process dysfunction as a nursing problem. The intervention consisted of health education on healthy gadget use and a demonstration of the Google Family Link application conducted over three sessions. Following the intervention, the average duration of gadget use among children decreased by 3.17 hours per day. In addition, families demonstrated improved abilities to monitor and regulate their children’s digital activities. These findings suggest that the implementation of Google Family Link, combined with family education, is effective in reducing excessive gadget use among school-age children and enhancing parental supervision and caregiving functions. Therefore, this intervention may serve as an alternative family nursing strategy to promote healthier digital behavior and support optimal child development in the digital age.